(untitled) (Huellas, 2023)
In Argentina, after the 2001 crisis, there was high economic growth, which resulted, among other improvements, in a significant decrease in the proportion of poor households in the 2001-2010 intercensal period - measured by the indicator of unsatisfied basic needs (UBN). The aim of this paper is to analyse the incidence of UBN on different types of households - using the variable "household types", composed of thirteen household types - as well as the changes in the relative share of each household type during the sharp decline in UBN between the 2001 and 2010 census years. To account for spatial inequality in the concentration of households and poverty in the territory, the variables are disaggregated at the provincial level and by districts/departments/communes. The results obtained show the relevance of considering changes in the composition of household types in the analysis of the incidence of poverty.